Vetëdija kulturore dhe politike e shqiptarëve në kohën e Lidhjes Shqiptare të Prizrenit - Nushi, Pajazit (Instituti i Historisë "Ali Hadri" Kosovë, 2025)
The scientific point of view at the time of the Albanian League of Prizren is clearly outlined and creates new outlooks in the intellectual, emotional, as well as the plan of action. In the intellectual plan, one can distinguish the development of the scientific thought on the truth, which is common for free life and the accomplishment of this goal through the development of education and culture in the Albanian language, the spread of this truth, and the organized efforts to create the nation-state under the complicated political relations and conditions between big powers and between Albanians and their neighbours. In the emotional plan, the love for the country and the nation became one with the genesis of the love for the nation-state. Regarding the plan of action, the organization of activities for the realization of the objectives of the General Council of the Albanian League of Prizren began. The scientific point of view was gaining greater importance (it primarily dealt with the political, economic, administrative, socio-cultural development of the Albanian nation and its language). The Albanian League of Prizren must be considered a factor in the consolidation and development of the scientific point of view among the Albanians. This is one of the most important achievements of the Albanian League of Prizren in the XIX century. The organisation of the Albanian League of Prizren gave power to the scientific thought comparing to the integration of the Albanian people and nation. Within this power, its practical application in the overall integrating processes was important. In support of the development of scientific thoughts, the establishment of different educational institutions in the Albanian language was envisaged, including the establishment of two universities and an academy of sciences. The Albanian League of Prizren opened new paths for the development of the creative thought by joining modern thought and by putting the latter into position acting against prejudices about the Albanians and the Albanian nation. The greatest opposition for the Albanian nation and state remained the academic thought between Albanians and Serbs. Despite the fact that the nation-state cannot be viewed any longer as it was viewed in the XIX century, the stance that an Albanian state poses a threat to the Balkans and Europe still prevails in the academic point of view and the official policy of Serbia. The Albanians respond to this model of thinking by applying the most appropriate forms of rule over themselves and embracing theoretical and practical challenges regarding freedom, union, and political and economic integration.